Choice and familiartity of using corridor and spill over space in urban centre - Tareg Ramadan Ali Bakra, 1980-; Dilshan Remaz Ossen, supervisor; Fakulti Alam Bina (2009)
Thesis (Sarjana Sains (Rekabentuk Bandar)) - Universiti Teknologi Malaysia, 2009